Oil well cementing slurry system and application thereof

CN119176694BActive Publication Date: 2026-10-27CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310743561.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-21
Publication Date
2026-10-27
Estimated Expiration
2043-06-21

AI Technical Summary

Technical Problem

[0005]本发明的目的是为了克服现有技术存在的水泥浆体系形成水泥石后,当养护温度超过150℃,加砂油井水泥因水化产物的转变导致水泥石强度降低和渗透率提高的问题,提供一种油井固井水泥浆体系及其应用,该水泥浆体系具有优异的抗高温强度衰退能力

Benefits of technology

[0011]本发明的水泥浆体系能够适应150-240℃地层温度环境,常规密度(1.88-1.9g/cm3)水泥浆体系凝固后形成的水泥石养护60d的抗压强度在35MPa以上,无强度衰退,且持续增长,具有良好的耐久性。本发明的水泥浆体系具有良好的保水和增稠性能,无需添加悬浮稳定剂即可保持水泥浆在高温条件下的悬浮稳定性。本发明的固井水泥浆体系采用常规方法混配,密度和稠化时间可调,流动性能好,失水量小,抗压强度和抗折强度高,且在高温下不衰退,完全满足现场固井施工的技术要求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the field of oil and gas well cementing, and discloses an oil well cementing slurry system and application thereof. The cementing slurry system comprises the following components in parts by weight: 100 parts of oil well cement, 20-80 parts of a high-temperature stabilizer, 15-80 parts of a high-temperature reinforcing agent, 0.5-6 parts of a retarder, 2-10 parts of a fluid loss reducer, 0.1-2 parts of a defoaming agent and 35-90 parts of water; wherein the high-temperature stabilizer is a mixture comprising quartz sand, micro-silicon powder and nano-silicon dioxide with different average particle sizes; and the high-temperature reinforcing agent is selected from at least one of pyrophyllite, epidote, actinolite, aluminum stone, eucolite and boehmite. The cementing slurry system is mixed by using a conventional method, the density and thickening time are adjustable, the flow performance is good, the water loss is small, the strength of the formed cement stone is high, and the cement stone does not degrade for a long time at a high temperature of 150-240 DEG C, and completely meets the technical requirements of deep and ultra-deep high-temperature and high-pressure cementing construction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of oil and gas well cementing, specifically to an oil well cementing slurry system and its application. Background Technology

[0002] my country possesses abundant and potentially significant deep and ultra-deep oil and gas resources. Statistics show that China's deep and ultra-deep oil and gas resources reach 671 × 10⁻⁶. 8 With an oil equivalent of 1 tonne, accounting for 34% of the total oil and gas resources, 39% of the remaining oil and 57% of the remaining natural gas resources are distributed in deep and ultra-deep formations. Accelerating the exploration and development of deep and ultra-deep oil and gas is a key focus and hot topic in current and future oil and gas exploration and development.

[0003] Cementing is a crucial step in the well construction process for oil and gas wells, serving as a prerequisite and foundation for the safe and efficient development of oil and gas resources. Cementing involves using equipment such as cement pump trucks to pump cement slurry through the drill pipe or casing into the annular space between the wellbore and casing, where it solidifies to form a hard cement sheath. This ultimately protects and suspends the casing, as well as isolates the formation, facilitating subsequent safe drilling and production. In deep and ultra-deep oil and gas exploration and development, complex environments such as high temperatures and high pressures are often encountered. The high-temperature strength degradation problem of silicate cement used in conventional oil and gas well cementing is one of the key factors affecting the quality of cementing in high-temperature deep wells. Studies have shown that 110℃ and 150℃ are the critical points for high-temperature strength degradation of cement stone. Adding 30%-40% quartz sand can maintain high-temperature strength stability within the 110-150℃ temperature range, but above 150℃, it only partially alleviates the strength degradation, but does not solve the problem.

[0004] Therefore, there is an urgent need for a cement slurry system that can form cement stone whose strength does not decline at temperatures above 150°C. Summary of the Invention

[0005] The purpose of this invention is to overcome the problem that in existing cement slurry systems, after the cement stone is formed, the strength of the cement stone decreases and the permeability increases due to the transformation of hydration products in sand-added oil well cement when the curing temperature exceeds 150°C. This invention provides an oil well cement slurry system and its application, which has excellent resistance to high-temperature strength degradation.

[0006] To achieve the above objectives, the first aspect of the present invention provides an oil well cementing slurry system, the cementing slurry system comprising the following components in parts by weight: 100 parts oil well cement, 20-80 parts high-temperature stabilizer, 15-80 parts high-temperature enhancer, 0.5-6 parts retarder, 2-10 parts fluid loss reducer, 0.1-2 parts defoamer, and 35-90 parts water;

[0007] The high-temperature stabilizer is a mixture comprising quartz sand, micro silica powder, and nano silica with different average particle sizes.

[0008] The high-temperature reinforcing agent is selected from at least one of pyrophyllite, epidote, actinolite, diaspore, sillimanite, and boehmite.

[0009] A second aspect of the present invention provides an application of the cement slurry system provided by the present invention in high-temperature deep well cementing.

[0010] The beneficial effects of the present invention through the above technical solution are as follows:

[0011] The cement slurry system of this invention can adapt to formation temperature environments of 150-240℃, with a conventional density of 1.88-1.9 g / cm³. 3 The cement slurry system, after solidification, forms cement stone with a compressive strength exceeding 35 MPa after 60 days of curing, exhibiting no strength degradation and continuous growth, demonstrating excellent durability. The cement slurry system of this invention possesses excellent water retention and thickening properties, maintaining its suspension stability under high-temperature conditions without the need for suspending stabilizers. The cement slurry system of this invention is formulated using conventional methods, with adjustable density and thickening time, good flowability, low water loss, high compressive and flexural strength, and no degradation at high temperatures, fully meeting the technical requirements of on-site cementing operations.

[0012] In a preferred embodiment of the present invention, by selecting appropriate sizes and proportions of quartz sand, microsilica powder, and nano-silica blends as high-temperature stabilizers, on the one hand, a dense packing effect is achieved through particle size distribution, improving the strength of the cement stone and reducing its porosity and permeability; on the other hand, the rate and process of silica participation in the hydration reaction are controlled by using crystalline quartz sand, amorphous microsilica powder, and nano-silica of different particle sizes. The present invention selects high-temperature reinforcing agents with reasonable combinations, raw material ratios, and sizes. The addition of high-temperature reinforcing agents can better inhibit the transformation of cement hydration products into high-calcium-silica ratio products, maintaining the dense structure of the cement stone. The present application selects appropriate types and sizes of toughening agents. The addition of toughening agents can, on the one hand, act as hydration nucleation points to induce hydration, and on the other hand, act as structural support points to improve the strength and toughness of the cement stone. The high-temperature stabilizers, high-temperature reinforcing agents, and toughening agents selected in this invention have a good synergistic effect, further improving the compressive strength of the cement stone formed by the cement paste system. Detailed Implementation

[0013] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0014] The first aspect of the present invention provides an oil well cementing slurry system, the cementing slurry system comprising the following components in parts by weight: 100 parts oil well cement, 20-80 parts high temperature stabilizer, 15-80 parts high temperature enhancer, 0.5-6 parts retarder, 2-10 parts fluid loss reducer, 0.1-2 parts defoamer, and 35-90 parts water;

[0015] The high-temperature stabilizer is a mixture comprising quartz sand, micro silica powder, and nano silica with different average particle sizes.

[0016] The high-temperature reinforcing agent is selected from at least one of pyrophyllite, epidote, actinolite, diaspore, sillimanite, and boehmite.

[0017] The use of quartz sand, microsilica, and nano-silica in high-temperature stabilizers achieves a dense packing effect through particle size distribution, improving the strength of cement stone while reducing its porosity and permeability. Furthermore, by using crystalline quartz sand, amorphous microsilica, and nano-silica of different particle sizes, the rate and process of silica participation in the hydration reaction are controlled, thereby increasing cement strength. The synergistic effect of quartz sand, microsilica, and nano-silica in improving cement stone strength is excellent. Pyrophyllite is a hydroxyl-containing aluminosilicate mineral, epidote is a hydroxyl-containing iron-aluminum-calcium silicate mineral, actinolite is a hydroxyl-containing iron-magnesium-calcium silicate mineral, sillimanite is a glassy aluminosilicate mineral with a columnar or acicular structure, and diaspore and boehmite are aluminum-rich bauxite. Using these minerals as high-temperature reinforcing agents can inhibit the transformation of cement hydration products into high-calcium-silica ratio products, maintaining the dense structure of the cement stone. The combination of high-temperature stabilizers and high-temperature reinforcing agents can improve the strength of cement. When high-temperature stabilizers and high-temperature reinforcing agents are combined with retarders, water loss reducers and defoamers, the resulting cement paste system has excellent resistance to high-temperature strength degradation.

[0018] According to a preferred embodiment of the present invention, the cement slurry system comprises the following components in parts by weight: 100 parts oil well cement, 40-50 parts high-temperature stabilizer, 30-40 parts high-temperature enhancer, 2.5-4.5 parts retarder, 7-8 parts water loss reducer, 0.4-0.6 parts defoamer, and 50-60 parts water.

[0019] According to the present invention, preferably, the oil well cement is grade G cement.

[0020] According to the present invention, preferably, the average particle size of the quartz sand is 75-180 μm, the average particle size of the microsilica powder is less than or equal to 10 μm, and the average particle size of the nano-silica is 1-100 nm. When the average particle sizes of the quartz sand, microsilica powder, and nano-silica meet this range, a good dense packing effect can be achieved through particle gradation, thereby improving the strength of the cement stone and reducing its porosity and permeability.

[0021] Furthermore, the average particle size of the quartz sand is 80-110 μm, the average particle size of the micro silica powder is 8-10 μm, and the average particle size of the nano silica is 20-30 nm.

[0022] According to the present invention, preferably, the weight ratio of the quartz sand, the microsilica powder, and the nano silica contained in the high-temperature stabilizer is (10-25):(3-5):1. When the quartz sand, microsilica powder, and nano silica are mixed in this weight ratio as a high-temperature stabilizer, the packing ratio can be increased, a dense packing effect can be achieved, and the structure of the cement stone can be improved.

[0023] According to the present invention, preferably, the average particle size of the high-temperature reinforcing agent is 5-80 μm. When the average particle size of the high-temperature reinforcing agent meets this range, it can improve the packing ratio, enhance the compact packing effect, maintain appropriate activity, and promote the transformation of hydration products.

[0024] According to the present invention, preferably, the high-temperature reinforcing agent is a mixture of epidote and boehmite, a mixture of pyrophyllite and sillimanite, or a mixture of pyrophyllite and actinolite. Using a mixture of epidote and boehmite as a high-temperature reinforcing agent, or using a mixture of pyrophyllite and sillimanite, a mixture of pyrophyllite and actinolite, or a mixture of pyrophyllite and actinolite as a high-temperature reinforcing agent, can synergistically enhance and inhibit the transformation of cement hydration products into high-calcium-silicon ratio products, and further inhibit the coarsening of the crystal structure of the hydration products.

[0025] According to the present invention, preferably, the high-temperature reinforcing agent is a mixture of epidote with an average particle size of 40-50 μm and boehmite with an average particle size of 10-15 μm, a mixture of pyrophyllite with an average particle size of 40-50 μm and sillimanite with an average particle size of 20-30 μm, or a mixture of pyrophyllite with an average particle size of 40-50 μm and actinolite with an average particle size of 70-80 μm.

[0026] According to the present invention, preferably, when the high-temperature reinforcing agent is a mixture of epidote and boehmite, the epidote and boehmite are mixed in a weight ratio of (20-30):(3-10); when the high-temperature reinforcing agent is a mixture of pyrophyllite and sillimanite, the pyrophyllite and sillimanite are mixed in a weight ratio of (20-30):(5-15); and when the high-temperature reinforcing agent is a mixture of pyrophyllite and actinolite, the pyrophyllite and actinolite are mixed in a weight ratio of (20-30):(5-20). When the high-temperature reinforcing agent is a mixture prepared according to the aforementioned proportions, it can synergistically enhance and inhibit the transformation of cement hydration products into high calcium-silica ratio products, and further inhibit the coarsening of the crystal structure of hydration products.

[0027] According to the present invention, preferably, the retarder is selected from at least one of inorganic acids, 2-acrylamido-2-methylpropanesulfonic acid (AMPS) multi-component copolymers, tartaric acid, citric acid, and phosphates, and more preferably a mixture of tartaric acid and AMPS multi-component copolymers. The AMPS multi-component copolymer can be a copolymer of 2-acrylamido-2-methylpropanesulfonic acid (AMPS), N-vinylpyrrolidone (NVP), and itaconic acid (LA). The present invention does not impose particular limitations on the weight-average molecular weight of the AMPS multi-component copolymer or the proportion of structural units contained in the AMPS multi-component copolymer, as long as it meets the performance requirements for a retarder. For example, AMPS multi-component copolymers purchased from the Texas Continental Shelf with the brand name SCR180L can be used. Using a mixture of tartaric acid and AMPS multi-component copolymers as a retarder can synergistically enhance the inhibition of cement hydration and improve the retarding effect under high-temperature conditions.

[0028] According to the present invention, preferably, the weight ratio of tartaric acid and AMPS multi-component copolymer is (1-5):(5-20). Mixing tartaric acid and AMPS multi-component copolymer in this weight ratio as a retarder can synergistically enhance the inhibitory effect on cement hydration and improve the retarding effect under high-temperature conditions.

[0029] According to the present invention, preferably, the water loss reducing agent is a polymer.

[0030] According to the present invention, preferably, the polymer is a copolymer comprising structural units derived from 2-acrylamido-2-methylpropanesulfonic acid (AMPS) and structural units derived from acrylamide.

[0031] This invention does not impose any particular restrictions on the weight-average molecular weight of the polymer, or on the weight ratio of structural units derived from 2-acrylamido-2-methylpropanesulfonic acid to structural units derived from acrylamide in the polymer, as long as the performance as a water loss reducing agent is met. For example, a copolymer of AMPS and acrylamide, purchased from the Texas Continental Shelf and brand name SCF-J, can be used.

[0032] According to the present invention, preferably, the defoamer is selected from silicone defoamers and / or tributyl phosphate defoamers. When the defoamer is a mixture of silicone defoamers and tributyl phosphate defoamers, the silicone defoamers and tributyl phosphate defoamers can be mixed in any proportion.

[0033] Furthermore, the defoamer is an organosilicon defoamer.

[0034] According to the present invention, preferably, the cement slurry system further comprises 5 parts by weight or less of a toughening agent. The high-temperature stabilizer can control the rate and process of silica participation in the hydration reaction, thereby improving the strength of the cement; the high-temperature reinforcing agent can inhibit the transformation of cement hydration products into high calcium-to-silica ratio products, maintaining the dense structure of the cement paste; the toughening agent can act as a hydration nucleation point to induce hydration, and on the other hand, it can act as a structural support point to improve the strength and toughness of the cement paste. When 5 parts by weight or less of a toughening agent is introduced into the cement slurry system, the high-temperature stabilizer, high-temperature reinforcing agent, and toughening agent can synergistically control the rate and type of hydration reaction products, further improving the high-temperature resistance of the cement slurry system.

[0035] Furthermore, the cement slurry system contains 0.5-1.5 parts by weight of toughening agent.

[0036] According to the present invention, preferably, the toughening agent is selected from fibers with a length of 1-19 mm and a diameter of 0.1-10 μm. Using fibers of this size as a toughening agent can enhance the toughness of cement stone and can also act as hydration nucleation sites to induce hydration.

[0037] According to the present invention, preferably, the fiber is selected from at least one of carbon fiber, boron fiber, and basalt fiber. Carbon fiber, boron fiber, and basalt fiber have the characteristics of high strength, high modulus, and high temperature resistance. When used as toughening agents, they can enhance the strength and toughness of cement stone, and at the same time, they can act as hydration nucleation sites to induce hydration.

[0038] According to a preferred embodiment of the present invention, the cement slurry system comprises the following components in parts by weight: 100 parts oil well cement, 20-80 parts high-temperature stabilizer, 15-80 parts high-temperature reinforcing agent, less than 5 parts toughening agent, 0.5-6 parts retarder, 2-10 parts water loss reducer, 0.1-2 parts defoamer, and 35-90 parts water.

[0039] According to a more preferred embodiment of the present invention, the cement slurry system comprises the following components in parts by weight: 100 parts oil well cement, 40-50 parts high-temperature stabilizer, 30-40 parts high-temperature reinforcing agent, 0.5-1.5 parts toughening agent, 2.5-4.5 parts retarder, 7-8 parts water loss reducer, 0.4-0.6 parts defoamer, and 50-60 parts water.

[0040] According to the present invention, preferably, the cement slurry system further comprises 2 parts by weight or less of a dispersant, more preferably 1 part by weight or less.

[0041] According to the present invention, preferably, the dispersant is selected from polycarboxylic acid dispersants and / or ketaldehyde condensates.

[0042] According to the present invention, preferably, the cement slurry system has a density of 1.88-1.9 g / cm³. 3 When solidified, the compressive strength after curing at 150-240℃ for 7 days is above 30MPa, the flexural strength is above 6MPa, and the compressive strength after 60 days is above 35MPa.

[0043] In a preferred embodiment of the present invention, the cement slurry system has a density of 1.88-1.9 g / cm³. 3 When solidified, the compressive strength after curing at 150-240℃ for 7 days is above 30MPa, the flexural strength is above 8MPa, and the compressive strength after 60 days is above 40MPa.

[0044] A second aspect of this invention provides an application of the cement slurry system provided by this invention in high-temperature deep well cementing, preferably in deep well cementing at a curing temperature of 150-240℃. The method of application is as follows: the cement slurry is applied to the deep well for cementing, solidifying into a cement ring in the annular space, and the compressive strength of the cement ring does not decline after 7-60 days.

[0045] The present invention will be described in detail below through examples. Unless otherwise specified, the reagents used in the following examples are all conventional biochemical reagents; the raw materials, instruments, and equipment used can all be obtained commercially or through existing methods; the reagent dosages, unless otherwise specified, are the dosages used in routine experimental operations; and the experimental methods, unless otherwise specified, are conventional methods. The reagents and determination methods involved in the following examples and comparative examples are as follows:

[0046] The oil well cement was Grade G cement purchased from Jiahua Cement Plant;

[0047] AMPS multi-component copolymer was purchased from the Texas Continental Shelf, with the grade SCR180L.

[0048] The water loss reducer is a copolymer of AMPS and acrylamide, purchased from the Texas Continental Shelf, brand name SCF-J;

[0049] Prepared according to GB / T 19139-2012 standard, with a density of 1.85-1.95 g / cm³. 3 Cement grout system;

[0050] The density of the cement paste system was determined according to the method specified in GB / T 19139-2012;

[0051] The fluidity of the cement slurry system was determined according to the method specified in GB / T 8077-2012;

[0052] The API water loss of the cement slurry system was determined according to the method specified in GB / T 19139-2012;

[0053] The thickening time of the cement slurry system was determined according to the method specified in GB / T 19139-2012;

[0054] The compressive strength of the cement grout system shall be determined according to the method specified in GB / T 19139-2012;

[0055] The flexural strength of the cement grout system was determined according to the method specified in GB / T 17671-2021.

[0056] The following examples illustrate the preparation of cement slurry systems.

[0057] Example 1

[0058] The cement slurry system comprises the following components in parts by weight: 100 parts oil well cement, 40 parts high-temperature stabilizer, 30 parts high-temperature reinforcing agent, 1.5 parts toughening agent, 2.5 parts retarder, 7 parts water loss reducer, 0.5 parts defoamer, and 59 parts water.

[0059] The high-temperature stabilizer is composed of quartz sand with an average particle size of 109 μm, quartz sand with an average particle size of 80 μm, micro silica powder with an average particle size of 9 μm, and nano silica with an average particle size of 25 nm in a weight ratio of 7:7:5:1.

[0060] The high-temperature reinforcing agent is composed of epidote with an average particle size of 48 μm and boehmite with an average particle size of 13 μm in a weight ratio of 25:5.

[0061] The toughening agent is basalt fiber with a length of 5 mm and a diameter of 8 μm;

[0062] The retarder is a mixture of tartaric acid and AMPS multi-component copolymer SCR180L in a weight ratio of 1:9.

[0063] The defoamer is a polysiloxane silicone defoamer (purchased from Texas Continental Shelf, brand name SCFD-2).

[0064] Example 2

[0065] The cement slurry system comprises the following components in parts by weight: 100 parts oil well cement, 40 parts high-temperature stabilizer, 35 parts high-temperature reinforcing agent, 0.5 parts toughening agent, 4.5 parts retarder, 8 parts water loss reducer, 0.5 parts defoamer, and 52 parts water.

[0066] The high-temperature stabilizer is composed of quartz sand with an average particle size of 109 μm, micro silica powder with an average particle size of 9 μm, and nano silica with an average particle size of 25 nm in a weight ratio of 15:4:1.

[0067] The high-temperature reinforcing agent is a mixture of pyrophyllite with an average particle size of 45 μm and sillimanite with an average particle size of 25 μm in a weight ratio of 25:10.

[0068] The toughening agent is carbon fiber with a length of 5 mm and a diameter of 6 μm;

[0069] The retarder, water loss reducer, and defoamer are the same as in Example 1.

[0070] Example 3

[0071] The cement slurry system comprises the following components in parts by weight: 100 parts oil well cement, 50 parts high-temperature stabilizer, 40 parts high-temperature reinforcing agent, 1.5 parts toughening agent, 4 parts retarder, 7 parts water loss reducer, 0.5 parts defoamer, and 51 parts water.

[0072] The high-temperature stabilizer is composed of quartz sand with an average particle size of 109 μm, micro silica powder with an average particle size of 9 μm, and nano silica with an average particle size of 25 nm in a weight ratio of 21:3:1.

[0073] The high-temperature reinforcing agent is composed of pyrophyllite with an average particle size of 45 μm and actinolite with an average particle size of 75 μm in a weight ratio of 25:10.

[0074] The toughening agent is basalt fiber with a length of 5 mm and a diameter of 8 μm;

[0075] The retarder, water loss reducer, and defoamer are the same as in Example 1.

[0076] Example 4

[0077] The cement slurry system was prepared according to the method in Example 2, except that the high-temperature stabilizer consisted of a mixture of quartz sand, microsilica powder, and nano-silica in a weight ratio of 8:4:1. The resulting cement slurry system was then obtained.

[0078] Example 5

[0079] The cement slurry system was prepared according to the method in Example 2, except that the average particle size of the quartz sand in the high-temperature stabilizer was 200 μm, the average particle size of the microsilica powder was 15 μm, and the average particle size of the nano-silica was 200 nm. The cement slurry system was thus obtained.

[0080] Example 6

[0081] The cement slurry system was prepared according to the method in Example 2, except that the average particle size of the quartz sand in the high-temperature stabilizer was 150 μm, the average particle size of the microsilica was 5 μm, and the average particle size of the nano-silica was 50 nm. The cement slurry system was thus obtained.

[0082] Example 7

[0083] The cement slurry system was prepared according to the method of Example 2, except that the high-temperature reinforcing agent was a mixture of pyrophyllite with an average particle size of 45 μm and sillimanite with an average particle size of 25 μm in a weight ratio of 25:20. The cement slurry system was thus obtained.

[0084] Example 8

[0085] The cement slurry system was prepared according to the method of Example 2, except that the high-temperature reinforcing agent was a mixture of pyrophyllite with an average particle size of 45 μm and boehmite with an average particle size of 13 μm in a weight ratio of 25:10. The cement slurry system was thus obtained.

[0086] Example 9

[0087] The cement slurry system was prepared according to the method in Example 2, except that polypropylene fiber (purchased from the Texas Continental Shelf, brand name SFP-2) was used as a toughening agent. The cement slurry system was thus obtained.

[0088] Example 10

[0089] The cement slurry system was prepared according to the method of Example 2, except that the amount of toughening agent was different. Specifically, the cement slurry system contained the following components in parts by weight: 100 parts oil well cement, 40 parts high-temperature stabilizer, 35 parts high-temperature reinforcing agent, 2 parts toughening agent, 4.5 parts retarder, 8 parts water loss reducing agent, 0.5 parts defoamer, and 52 parts water.

[0090] Example 11

[0091] The cement slurry system was prepared according to the method of Example 2, except that the weight percentage of the high-temperature stabilizer was different. Specifically, the cement slurry system contained the following components in parts by weight: 100 parts oil well cement, 80 parts high-temperature stabilizer, 35 parts high-temperature reinforcing agent, 0.5 parts toughening agent, 4.5 parts retarder, 8 parts water loss reducing agent, 0.5 parts defoamer, and 68 parts water.

[0092] Comparative Example 1

[0093] The cement slurry system was prepared according to the method of Example 2, except that the cement slurry system did not contain high-temperature reinforcing agents or toughening agents, and the high-temperature stabilizer did not contain microsilica powder or nano-silica. Specifically, the cement slurry system contained the following components in parts by weight: 100 parts oil well cement, 40 parts quartz sand with an average particle size of 109 μm, 4.5 parts retarder, 8 parts water loss reducing agent, 0.5 parts defoamer, and 38 parts water, resulting in a density of 1.9 g / cm³. 3 The cement slurry system.

[0094] Comparative Example 2

[0095] The cement slurry system was prepared according to the method of Example 2, except that it did not contain high-temperature reinforcing agents or toughening agents. Specifically, the cement slurry system contained the following components in parts by weight: 100 parts oil well cement, 40 parts high-temperature stabilizer, 4.5 parts retarder, 8 parts water loss reducing agent, 0.5 parts defoamer, and 38 parts water, resulting in a density of 1.9 g / cm³. 3 The cement slurry system.

[0096] Comparative Example 3

[0097] The cement slurry system was prepared according to the method of Example 2, except that the weight percentage of the high-temperature reinforcing agent in the cement slurry system was different. Specifically, the cement slurry system contained the following components in parts by weight: 100 parts oil well cement, 40 parts high-temperature stabilizer, 5 parts high-temperature reinforcing agent, 0.5 parts toughening agent, 4.5 parts retarder, 8 parts water loss reducing agent, 0.5 parts defoamer, and 40 parts water, resulting in a density of 1.9 g / cm³. 3 The cement slurry system.

[0098] Comparative Example 4

[0099] The cement slurry system was prepared according to the method of Example 2, except that the weight percentage of the high-temperature stabilizer in the cement slurry system was different. Specifically, the cement slurry system contained the following components in parts by weight: 100 parts oil well cement, 10 parts high-temperature stabilizer, 35 parts high-temperature reinforcing agent, 0.5 parts toughening agent, 4.5 parts retarder, 8 parts water loss reducing agent, 0.5 parts defoamer, and 40 parts water, resulting in a density of 1.9 g / cm³. 3 The cement slurry system.

[0100] Comparative Example 5

[0101] The cement slurry system was prepared according to the method in Example 2, except that the high-temperature stabilizer did not contain microsilica powder or nano-silica. Specifically, the cement slurry system contained the following components in parts by weight: 100 parts oil well cement, 40 parts quartz sand with an average particle size of 109 μm, 35 parts high-temperature reinforcing agent, 0.5 parts toughening agent, 4.5 parts retarder, 8 parts water loss reducing agent, 0.5 parts defoamer, and 52 parts water. The resulting cement slurry system contained some sediment and exhibited poor suspension stability.

[0102] Comparative Example 6

[0103] The cement slurry system was prepared according to the method in Example 2, except that α-Al₂O₃ with an average particle size of 50 μm was selected as the high-temperature reinforcing agent. The cement slurry system was thus obtained.

[0104] Test case

[0105] The density, fluidity, API water loss, thickening time, compressive strength and flexural strength of the cement paste system prepared in each example and comparative example were measured after curing at 150-240℃ for 7-60 days. The results are shown in Table 1.

[0106] Table 1

[0107]

[0108] As can be seen from the above embodiments, comparative examples, and Table 1, the high-temperature strength degradation resistant cement slurry system of the present invention has adjustable density and thickening time, good flowability, low water loss, and high strength cement stone formed after hardening. Its compressive strength after curing at 150-240℃ for 7 days is above 30 MPa, and it does not degrade at high temperatures. The conventional density obtained in Example 2 is 1.88-1.9 g / cm³. 3 The cement stone formed by the cement slurry system exhibited compressive strengths above 40 MPa after curing at 220℃ and 240℃ for 30 and 60 days, respectively. In contrast, the cement stone formed by the cement slurry systems prepared in Comparative Examples 1-4 showed a compressive strength below 21 MPa after curing at 220℃ for 7 days, and exhibited long-term strength degradation. Comparative Example 5 showed poor slurry suspension stability and sand sedimentation. Therefore, the cement slurry system of this invention is far superior to conventional sand-added cement systems and fully meets the technical requirements for deep and ultra-deep high-temperature and high-pressure cementing operations.

[0109] Furthermore, Example 4 changed the weight ratio of quartz sand, microsilica powder, and nano-silica in the high-temperature stabilizer; Examples 5 and 6 changed the average particle size of quartz sand, microsilica powder, and nano-silica in the high-temperature stabilizer; Example 7 changed the weight ratio of pyrophyllite and sillimanite in the high-temperature reinforcing agent; Example 8 changed the combination of the high-temperature reinforcing agent; Example 9 changed the type of toughening agent; Example 10 changed the amount of toughening agent; and Example 11 changed the amount of high-temperature stabilizer. Compared with Example 2, the compressive strength cured for 7 days at 150-240℃ was reduced, but it did not decline at high temperatures and continued to increase. This indicates that the high-temperature stabilizer, high-temperature reinforcing agent, and toughening agent selected in this invention have a good synergistic effect within a certain ratio range, which can further improve the compressive strength of the cement paste system at high temperatures after solidification.

[0110] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combining the various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. An oil well cementing slurry system, characterized in that, The cement slurry system comprises the following components in parts by weight: 100 parts oil well cement, 20-80 parts high-temperature stabilizer, 15-80 parts high-temperature enhancer, 0.5-6 parts retarder, 2-10 parts water loss reducer, 0.1-2 parts defoamer, and 35-90 parts water. The high-temperature stabilizer is composed of quartz sand, microsilica powder and nano silica with different average particle sizes. The average particle size of the quartz sand is 75-180μm, the average particle size of the microsilica powder is less than or equal to 10μm, and the average particle size of the nano silica is 1-100nm; the weight ratio of the quartz sand, the microsilica powder and the nano silica contained in the high temperature stabilizer is (10-25):(3-5):

1. The high-temperature reinforcing agent is a mixture of epidote with an average particle size of 40-50 μm and boehmite with an average particle size of 10-15 μm, or a mixture of pyrophyllite with an average particle size of 40-50 μm and sillimanite with an average particle size of 20-30 μm, or a mixture of pyrophyllite with an average particle size of 40-50 μm and actinolite with an average particle size of 70-80 μm. When the high-temperature reinforcing agent is a mixture of epidote and boehmite, the weight ratio of epidote to boehmite is (20-30):(3-10); when the high-temperature reinforcing agent is a mixture of pyrophyllite and sillimanite, the weight ratio of pyrophyllite to sillimanite is (20-30):(5-15); when the high-temperature reinforcing agent is a mixture of pyrophyllite and actinolite, the weight ratio of pyrophyllite to actinolite is (20-30):(5-20). The cement slurry system also contains less than 5 parts by weight of toughening agent; The toughening agent is selected from fibers with a length of 1-19 mm and a diameter of 0.1-10 μm; The fiber is selected from at least one of carbon fiber, boron fiber and basalt fiber.

2. The cement slurry system according to claim 1, characterized in that, The retarder is selected from at least one of inorganic acids, 2-acrylamido-2-methylpropanesulfonic acid copolymers, tartaric acid, citric acid, and phosphates.

3. The cement slurry system according to claim 2, characterized in that, The retarder is a mixture of tartaric acid and a 2-acrylamido-2-methylpropanesulfonic acid multi-component copolymer.

4. The cement slurry system according to claim 3, characterized in that, The weight ratio of the tartaric acid and the 2-acrylamido-2-methylpropanesulfonic acid multi-component copolymer is (1-5):(5-20).

5. The cement slurry system according to any one of claims 1-4, characterized in that, The water loss reducing agent is a polymer.

6. The cement slurry system according to claim 5, characterized in that, The polymer is a copolymer comprising structural units derived from 2-acrylamido-2-methylpropanesulfonic acid and structural units derived from acrylamide.

7. The cement slurry system according to any one of claims 1-4, characterized in that, The defoamer is selected from silicone defoamers and / or tributyl phosphate defoamers.

8. The cement slurry system according to claim 1, characterized in that, The cement slurry system comprises the following components in parts by weight: 100 parts oil well cement, 40-50 parts high-temperature stabilizer, 30-40 parts high-temperature reinforcing agent, 0.5-1.5 parts toughening agent, 2.5-4.5 parts retarder, 7-8 parts water loss reducer, 0.4-0.6 parts defoamer, and 50-60 parts water.

9. The cement slurry system according to any one of claims 1-4, characterized in that, The cement slurry system also contains less than 2 parts by weight of dispersant.

10. The cement slurry system according to claim 9, characterized in that, The dispersant is selected from polycarboxylic acid dispersants and / or ketaldehyde condensates.

11. The cement slurry system according to any one of claims 1-4, characterized in that, The cement slurry system has a density of 1.88-1.9 g / cm³. 3 When solidified, the compressive strength after curing at 150-240℃ for 7 days is above 30MPa, the flexural strength is above 6MPa, and the compressive strength after 60 days is above 35MPa.

12. The cement slurry system according to claim 11, characterized in that, The cement slurry system has a density of 1.88-1.9 g / cm³. 3 When solidified, the compressive strength after curing at 150-240℃ for 7 days is above 30MPa, the flexural strength is above 8MPa, and the compressive strength after 60 days is above 40MPa.

13. The application of the cement slurry system according to any one of claims 1-12 in high-temperature deep well cementing.

14. The application according to claim 13, wherein, The cement slurry system is used in deep well cementing at a curing temperature of 150-240℃.

Citation Information

Patent Citations

  • High-strength high-toughness high-temperature-resistant oil well cement slurry system as well as preparation method and design method thereof

    CN106833567A

  • Ultrahigh-strength tough cement paste system for well cementation as well as preparation and application thereof

    CN112939527A

  • Large-temperature-difference well cementation cement paste and preparation method thereof

    CN114380540A